'Cris nouveaux': The Soundscape of Paris in Mercier's Tableau de Paris and Le Nouveau Paris. Issue 1 (2nd January 2019) - Darlow, Mark
Abstract : Although Louis-Sébastien Mercier's Tableau de Paris and Le Nouveau Paris are framed in visual terms, the attention to types of sound in these works is sustained and detailed. Tracing Mercier's descriptions of different types of sound, for instance noise, human voices, or music, I argue that Mercier offers us a soundscape of pre-Revolutionary and Revolutionary Paris. Sound is used by Mercier as a means of mapping the various topographies of Paris, whether social, cultural, or moral. Through its soundscape, Le Nouveau Paris insists on how much Paris had changed by 1798, and Mercier's depictions of chaos and cacophony suggest a world out of tune; they also allow us to trace his nostalgia for the Paris which had been swept away by the Revolutionary events.